2020
DOI: 10.3390/ijerph17010302
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Koreans on Sleep Habits and Sleeping Symptoms Relating to Pillow Comfort and Support

Abstract: The number of people who complain of sleep disturbances is steadily increasing. An understanding of sleep-related factors is required to address sleep problems. This survey study investigated the sleep habits and sleeping symptoms relating to the comfort and support characteristics of pillows and the relationship between sleep quality and pillow design factors. The study utilized data from 332 participating Korean adults aged 20–76 years (mean age ± SD: males, 40.4 ± 15.2; females, 42.9 ± 15.4). We developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Some sleep issues may be mitigated by choosing an appropriate pillow type, e.g., with an appropriate pillow neck and side height [24], and sleepwear fabric type, e.g., sleeping in wool promoted improved sleep [25,26]. The food type consumed may also help to promote sleep onset, e.g., a high glycemic index meal shortened sleep onset compared to a low glycemic index meal [27].…”
mentioning
confidence: 99%
“…Some sleep issues may be mitigated by choosing an appropriate pillow type, e.g., with an appropriate pillow neck and side height [24], and sleepwear fabric type, e.g., sleeping in wool promoted improved sleep [25,26]. The food type consumed may also help to promote sleep onset, e.g., a high glycemic index meal shortened sleep onset compared to a low glycemic index meal [27].…”
mentioning
confidence: 99%
“…After the termination of the tests, the participants were asked to rate their main subjective perceptions in using the InPillow, that is, contact comfort, 28 which was scaled from −3 (very discomfort) to 0 (comfort). 30 Table 2 lists the accuracy values of heart-rate detection of the 14 subjects within the 5 min testing. The accuracy values range from 98.06% to 99.73%, with the average value and standard deviation of 99.18% and 0.55%, respectively.…”
Section: Accuracy Validation and Testing The Inpillow In Real-scenariomentioning
confidence: 99%
“…i = 0, 1,. . ...15); (2) Design a moving time domain window (width: 3 s; moving step length: 2 s), and determine the maximum peak in each window; (3) If the maximum peak in a window is higher than that in the previous window, body movement occurs, and the number of body movements was recorded 29,30. Figure3displayed the original vital signals and separated BCG, respiratory, and body movement signals collected by the novel intelligent pillow.…”
mentioning
confidence: 99%
“…Previous research has suggested that the use of custom fitted pillows may represent an efficacious and cost-effective treatment option in mild to moderate OSAS ( 10 ), filling a niche where continuous positive airway pressure (CPAP) would not be indicated ( 11 ). Considering that pillow design can be guided ( 12 , 13 ) to alleviate specific symptoms, an evaluation of pillow type impact on sleep health may be directly relevant to their efficacious implementation.…”
Section: Introductionmentioning
confidence: 99%